2020
DOI: 10.1111/jsr.13064
|View full text |Cite
|
Sign up to set email alerts
|

Subjective–objective sleep discrepancy in patients with insomnia during and after cognitive behavioural therapy: An actigraphy study

Abstract: Although patients with insomnia often show a discrepancy between self-reported and objective sleep parameters, the role of and change in this phenomenon during treatment remain unclear. The present study aimed to assess the effect of cognitive behavioural therapy for insomnia on subjective and objective sleep discrepancy of total sleep time, sleep-onset latency and wake after sleep onset. The total sleep time discrepancy was also assessed across the entire therapy. The second aim was to examine the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
19
1
Order By: Relevance
“…These findings indicate the importance of a waitlist control group and could indicate regression to the mean, first night effects, or perhaps a learning effect where studies that draw participant attention to sleep variables may influence subjective responses over time, irrespective of treatment interventions. These results contrast with previous studies in insomnia samples that found evidence for a reduction of SOSD after CBT-I [14,23,25,47,48].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings indicate the importance of a waitlist control group and could indicate regression to the mean, first night effects, or perhaps a learning effect where studies that draw participant attention to sleep variables may influence subjective responses over time, irrespective of treatment interventions. These results contrast with previous studies in insomnia samples that found evidence for a reduction of SOSD after CBT-I [14,23,25,47,48].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported that CBT-I reduces the discrepancy between subjective and objective measures of sleep in individuals with insomnia alone [14,23,25,46]. This is likely driven by a large improvement in subjective sleep estimates, and minimal change in objective sleep during treatment that results in a convergence of the two measures post CBT-I-treatment but could also be explained by regression to the mean [23,24].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…After 6‐week of the CBT‐i program, Janků and colleagues reported a significant reduction of total sleep time discrepancy. On the other hand, change in wake after sleep onset discrepancy was not observed 41 …”
Section: Non‐pharmacologic Therapiesmentioning
confidence: 75%